1, 3‐Propane Diamine/1, 4‐Butane Diamine Cross‐linking Modification of Polyimide Membrane for Hydrogen Selective Separation: Effect of Diamine Mixture Ratio. Issue 3 (24th January 2020) - Abdul Nasir, Nur'Adilah; Ling, Jia Hui; Junaidi, Mohd Usman Mohd; Hashim, Nur Awanis; Hizzaddin, Hanee Farzana; Rabuni, Mohamad Fairus; Zainal Abidin, Mohd Izzuddin Izzat; Rohani, Rosiah
Abstract: Hydrogen (H2 ) can be produced through biomass processing which involved lower energy requirement and production cost. It is produced as biohydrogen (bio‐H2 ) together with carbon dioxide in biogas so it is essential to purify H2 for utilization. Membrane gas separation is a promising technology for H2 purification. However, current separation efficiency of commercial polymeric membrane is insufficient to achieve industrial demand. Crosslinking diamine modification has been discovered to enhance separation performance of membrane in terms of permeability and selectivity. Gas separation effectiveness of mixed crosslinking agent on polyimide (PI) membrane is studied in this research by blending PDA and BuDA with different concentration. PI membrane is fabricated with phase inversion method with different weight percentage of PI in polymer solution. The chemical modification by immersing in mixed PDA‐BuDA crosslinking solution for 5 minutes reaction times. Pure gas test has been conducted for separation performance andchemical structure changes were monitored by FTIR. It is found that H2 /CO2 selectivity increased significantly and H2 permeability decreased dramatically with higher concentration of PDA in crosslinking solution. Membrane with 8:2 ratio of PDA‐BuDA solution achieved highest H2 /CO2 selectivity from 3.7 to 7.8 compared to other ratio of PDA‐BuDA solution.